STEM education in schools: Teachers’ readiness to change - Abd Rauf, Rose Amnah; Sathasivam, Renuka V.; Abdul Rahim, Suzieleez Syrene (Taylor's University, 2019)
Change is an important aspect for the implementation of STEM education in school. For teachers to implement STEM, they should have readiness to change and to have no resistance to change. However, teachers are still teaching for examination purposes regardless of the efforts from the Ministry urging them to change. Thus, the aim of this study was to investigate 20 science teachers and 18 pre-service teachers’ readiness to change and resistance to change with regards to STEM implementation. The participants were involved in the STEMBuild Training of Trainers (TOT) Program. The program consisted of three phases, which were: conception of STEM, knowledge building, and practical implementation. The content of the program was in-line with the Malaysian primary school curriculum. This was a pre-experimental design study because it involved only one group. Change beliefs scale and resistance to change scale were administered after the program. For the change beliefs scale the teachers had the highest mean score for Personal Valence and lowest mean score for Self-efficacy. Even though these two subscales of change beliefs showed opposite direction of belief towards change, the participants mean scores of the overall change beliefs was high which indicated a positive inclination towards the change. In terms of resistance to change scale, the teachers were generally supporters of the change. The findings revealed that the participants were ready to carry out the STEM activities in school, they adhered to the belief for this change and their resistance to change was minimal. © School of Engineering, Taylor’s University.